Heparin-Induced Thrombocytopenia Complicating Thrombotic Thrombocytopenic Purpura - Galila F. Zaher,; Maha A. Badawi, (Journal of King Abdulaziz University: Medical Sciences, 2023)
Since the introduction of therapeutic plasma exchange for the management of thrombotic thrombocytopenic purpura, the prognosis of this disease improved signifi cantly. Some patients suffer from refractory disease and adjunctive therapy needs to be considered. In addition, alternative explanations for thrombocytopenia may be present. In this report we discuss a patient who presented with typical fi ndings of thrombotic thrombocytopenic purpura and responded initially to therapeutic plasma exchange and steroids. Shortly afterwards, his platelet count deteriorated and he was found to have acute pulmonary embolism. Prior to the pulmonary embolism, the patient had received venous thromboembolism prophylaxis in the form of low molecular weight heparin and had a history of previous exposure to unfractionated heparin. Testing for heparin-induced thrombocytopenia antibodies was positive and the patient was started on an alternative anticoagulant. Despite these early interventions the patient did not survive. It is essential that physicians be aware of such possible associations to request appropriate investigations and start appropriate management, accordingly.